2005
DOI: 10.1158/0008-5472.can-04-4424
|View full text |Cite
|
Sign up to set email alerts
|

Src Homology 2–Containing Inositol 5′-Phosphatase 1 Negatively Regulates IFN-γ Production by Natural Killer Cells Stimulated with Antibody-Coated Tumor Cells and Interleukin-12

Abstract: We have previously shown that natural killer (NK) cells secrete a distinct profile of immunomodulatory cytokines in response to dual stimulation with antibody-coated tumor cells and interleukin-12 (IL-12). This NK cell cytokine response is dependent on synergistic signals mediated by the activating receptor for the Fc portion of IgG (Fc;RIIIa) and the IL-12 receptor (IL-12R), both constitutively expressed on NK cells. The phosphatase Src homology 2-containing inositol 5V -phosphatase 1 (SHIP1) is known to exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 49 publications
2
23
0
Order By: Relevance
“…44 Similarly, SHIP1-deficient mouse NK cells produced greater amount of IFN-␥ upon stimulation with Abcoated tumor cells plus IL-12. 27 In conclusion, the discrepancy we report here between normal intracellular production and reduced secretion of IFN-␥ and other cytokines by p110␦-deficient NK cells suggests that PI3K isoforms control signaling checkpoints during the progression from cytokine gene transcription to secretion in mouse NK cells. PI3K p110␦ emerges as the dominant isoform for cytokine secretion by NK cells.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…44 Similarly, SHIP1-deficient mouse NK cells produced greater amount of IFN-␥ upon stimulation with Abcoated tumor cells plus IL-12. 27 In conclusion, the discrepancy we report here between normal intracellular production and reduced secretion of IFN-␥ and other cytokines by p110␦-deficient NK cells suggests that PI3K isoforms control signaling checkpoints during the progression from cytokine gene transcription to secretion in mouse NK cells. PI3K p110␦ emerges as the dominant isoform for cytokine secretion by NK cells.…”
Section: Discussionmentioning
confidence: 54%
“…26 That PI3Ks mediate cytokine production in NK cells is also highlighted by the increased production in mice lacking a negative regulator of PI3K, Src homology 2-containing inositol 5Ј-phosphatase 1 (SHIP-1). 27 However, these findings have not yet been validated in vivo in PI3K mutant mice, nor has the issue of PI3K isoform specificity been addressed in NK cells, except for our recent work showing that p110␦ is essential for NK cell immunity to transplanted lymphomas. 28 The only other references to NK cell biology found in published studies of PI3K mutant mice reported no defect in NK-cell development or differentiation in p85␣-deficient mice.…”
Section: Introductionmentioning
confidence: 97%
“…Because SHIP1 normally targets the PI-3K lipid product phosphatidylinositol 3,4,5-trisphosphate (PI3,4,5P 3 ), 29 its suppression in miR-155 tg NK cells, in fact, leads to enhanced ERK activation. 10,30,41 One aspect of miR-mediated gene regulation is that each specific miR is predicted to target hundreds of genes. 42 As miR-155 has multiple targets, it is very likely that the mechanism and observed effects of miR-155 overexpression on NK-cell development, homeostasis, and function are not yet completely understood.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of SHIP1 expression in resting and IL-12 and/or IL-18 activated primary human NK cells SHIP1 5Ј inositol phosphatase is a negative regulator of IFN-␥ in both human and mouse NK cells, 13,16 and a primary target of miR-155. 28,32,33 To address whether there is an inverse correlation between SHIP1 expression and miR-155 expression in NK cells, we first analyzed SHIP1 mRNA and protein expression in primary NK cells stimulated with IL-12 and/or IL-18.…”
Section: The Role Of Mir-155 In the Regulation Of Ifn-␥ Production Bymentioning
confidence: 99%
“…13 SHIP1, by dampening the PI3K pathway, is able to negatively regulate IFN-␥ production by monokines and CD16 stimulation in both human and mouse NK cells. 13,16 MicroRNAs (miRs) are a highly conserved class of small, noncoding RNAs with important regulatory functions in proliferation, differentiation, signal transduction, immune responses, and carcinogenesis. 17 miRs regulate gene expression posttranscriptionally by forming imperfect base pairs with sequences in the 3Ј untranslated region (UTR) of genes.…”
Section: Introductionmentioning
confidence: 99%